Role of Krüppel-Like Factor 4 in Neurogenesis and Radial Neuronal Migration in the Developing Cerebral Cortex - Qin, Song (American Society for Microbiology, 2012)
Transcription factors play key roles in the formation of a multilayered cerebral cortex consisting of neurons and glial cells. Krüppel-like factor 4 (KLF4) is expressed in neural stem cells and controls axonal regeneration. Its dysregulation leads to hydrocephalus in postnatal mouse brains. Here, we further show that KLF4 regulates neurogenesis and radial migration of neurons in the developing cerebral cortex. Neural progenitors with constitutive expression of KLF4 fail to migrate and develop into mature neurons but, rather, form cells with a glial identity. Notably, the JAK-STAT pathway is altered by KLF4, with increased phosphorylation of STAT3 at tyrosine 705. Blocking STAT3 activation with a dominant negative form can rescue the migration defect induced by constitutive KLF4 expression. Furthermore, downregulation of endogenous KLF4 significantly promotes radial migration and the transition of newly born migrating neurons from multipolar to bipolar morphology. Together, these results suggest that precise regulation of KLF4 expression is critical to neuronal differentiation and migration during the formation of a cerebral cortex.